STRATEGI PENGENALAN MANAJEMEN SERTIFIKASI HALAL DALAM MENINGKATKAN KUALITAS PRODUK USAHA MIKRO KECIL DAN MENENGAH DI DESA CIBITUNG TENGAH, KECAMATAN TENJOLAYA, KABUPATEN BOGOR - Rully Trihantana; Ermi Suryani; Puloh (SAHID EMPOWERMENT JOURNAL, 2022)
This community service aims to introduce halal certification management in improving the quality of Micro, Small and Medium Enterprises (MSMEs) products. The subject of this community service is the people of Central Cibitung Village, Pamijahan District, Bogor Regency, West Java Province. In community service, activities are carried out based on interactive socialization methods. The result of this community service is that there will be a socialization of halal certification management by involving the Village of Central Cibitung and the Halal Study Center of the Sahid Bogor Islamic Institute, then a process of assistance and supervision will be carried out in the creation of the Halal Assurance System. With this community service, it can be concluded that this activity aims to improve the quality of MSME products in Central Cibitung Village by evaluating activities after they were carried out during the introduction of halal certification management.